HEALTH OF URBAN POPULATION IN MOSCOW AND BEIJING AGGLOMERETIONS - Svetlana M. Malkhazova; Yang Linsheng; Wang Wuyi; Dmitry S. Orlov; Natalia V. Shartova; Li Hairong; Wang Li (Geography, Environment, Sustainability, 2014)
The paper presents the results obtained under the joint Russian-Chinese RFBR project № 12-05-91175-ГФЕН_а aimed at assessment of the state of the environment and health of the population in urban areas in Russia and China. The paper presents the authors’ approach to a comprehensive evaluation of the impact of the environment on the populationhealth of urban agglomerations and a method of regional medico-geographical analysis. A series of analytical and synthetic maps was compiled and used for a comparative geographical analysis of medical and environmental situation in Moscow and Beijing – major metropolitan areas with different natural and socio-economic conditions. The paper discusses the influence of the environment on the state of public health and identifies the leading risk factors, both general and specific to each region.